PENERAPAN PEMBELAJARAN CTL DALAM MENGASAH PENALARAN MATEMATIS SISWA PADA MATERI RELASI DAN FUNGSI: Application Of CTL Learning In Honing Students' Mathematical Reasoning On Relation and Function Material - Putri, Resky; Hasanuddin, Hasanuddin (Yayasan Al-Amin Qalbu, 2025)
This study aims to evaluate the effect of implementing Contextual Teaching and Learning (CTL) approach on mathematical reasoning ability of grade VIII students on relation and function material in one of the junior high schools in Pangkalan Kerinci. This study used a qualitative approach with descriptive method, involving one class of 20 students. Data collection techniques were conducted through interviews and observations, focusing on students' ability to express CTL-based learning concepts. Evaluation was conducted on three main aspects, namely students' mathematical reasoning ability, teachers' competence in facilitating learning, and students' responses to the implementation of CTL learning. The results showed that about 20% of students reached the excellent category in mathematical reasoning, characterized by the achievement of the five reasoning indicators. Although there are still some students with less than optimal reasoning skills, in general, the application of CTL models is proven effective in increasing students' learning motivation, concept understanding, and mathematical reasoning skills. This finding confirms that context-based learning is able to provide a more meaningful and relevant learning experience, and become a potential alternative strategy in an effort to improve the quality of mathematics learning at the junior high school level.